Cancer Detection: Microneedle Biosensor for Real‐Time Electrical Detection of Nitric Oxide for In Situ Cancer Diagnosis During Endomicroscopy (Adv. Healthcare Mater. 8/2015). Issue 8 (3rd June 2015) - Keum, Do Hee; Jung, Ho Sang; Wang, Taejun; Shin, Myeong Hwan; Kim, Young‐Eun; Kim, Ki Hean; Ahn, G‐One; Hahn, Sei Kwang
<x xml:space="preserve">Abstract</x> A novel microneedle biosensor is developed on page 1153 for real‐time electrical detection of nitric oxide (NO) for in situ cancer diagnosis during endomicroscopy. S. K. Hahn and co‐workers show that the dual diagnostic system of endomicroscope and microneedle biosensor demonstrates high resolution imaging combined with electrical detection of NO released from cancer tissues as a new platform for facile, rapid, and accurate diagnosis of cancers.